2014
DOI: 10.1002/anie.201406216
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Mediated Assembly of Phototherapeutics

Abstract: Light-activatable drugs offer the promise of controlled release with exquisite temporal and spatial resolution. However, light sensitive pro-drugs are typically converted to their active forms using short wavelengths, which display poor tissue penetrance. We report herein erythrocyte-mediated assembly of long wavelength-sensitive phototherapeutics. The activating wavelength of the constructs is readily pre-assigned by using fluorophores with the desired λex. Drug release from the erythrocyte carrier was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…33 For our initial studies, we chose ethyl-cobalamin (EtCbl) due to its reported high quantum yield of photohomolysis (~0.3), 32 but it may be possible to use other primary alkyl ligands, such as aminopropyl, for dual photopolymerization and functionalization of hydrogels. 30,31 The EtCbl-ethylenediamine 5 intermediate is derived from Zn-mediated reduction of 4 to a supernucleophilic Co I species and subsequent alkylation with ethyl bromide. 34 Photoinitiator 1 ( ε ~ 8500 M −1 cm −1 , λ max ~ 510 nm, Figure 1) was prepared by reacting the free amine of 4 with acetic anhydride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 For our initial studies, we chose ethyl-cobalamin (EtCbl) due to its reported high quantum yield of photohomolysis (~0.3), 32 but it may be possible to use other primary alkyl ligands, such as aminopropyl, for dual photopolymerization and functionalization of hydrogels. 30,31 The EtCbl-ethylenediamine 5 intermediate is derived from Zn-mediated reduction of 4 to a supernucleophilic Co I species and subsequent alkylation with ethyl bromide. 34 Photoinitiator 1 ( ε ~ 8500 M −1 cm −1 , λ max ~ 510 nm, Figure 1) was prepared by reacting the free amine of 4 with acetic anhydride.…”
Section: Resultsmentioning
confidence: 99%
“…29 Recently, we reported the NIR induced scission of weak cobalt–carbon bonds present in vitamin B 12 -derived alkyl-cobalamins (Co–C; bond dissociation energy ~ 30 kcal/mol). 30,31 Normally, excitation of unmodified alkyl-cobalamins ( λ ex ~ 510 nm) induces a metal-to-ligand charge transfer that decays to a dissociative alkyl radical and cobalt(II) species with high quantum yields (Φ ~ 20–40%). 32 However, despite lacking absorption longer than 600 nm, alkyl-cobalamin photolysis in the red, far red, and NIR can be achieved by excitation of covalently linked or noncovalently associated fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…[6] B12 is not membrane permeable, but rather is transported into cells via a sophisticated protein carrier, receptor-mediated, endosome-dependent mechanism. [7] We wondered whether Cbl-bioagent conjugates might retain the membrane impermeability properties of the parent B12 and thus could be ensconced within lipid-enclosed compartments until needed.…”
mentioning
confidence: 99%
“…Previously, we’ve shown that the light responsiveness of Cbl conjugates can be tuned to specific wavelengths deep into the red, far red, and near IR. [6b] These wavelengths penetrate tissue more effectively than UV and short visible wavelengths, a decided advantage under in vivo conditions. [8] With these features in mind, we chose the interior of erythrocytes as a membrane enclosed environment to explore the conjecture that illumination can be used to control the secretion of biologically active compounds (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation